EFEKTIVITAS PENGGUNAAN MEDIA STICK POUCH (KANTONG STIK) TERHADAP MOTIVASI BELAJAR SISSWA KELAS II SDN PANNARA KOTA MAKASSAR - Hilda Hilda; Waddi Fatimah; Perawati Bte Abustang (JKPD (Jurnal Kajian Pendidikan Dasar), 2023)
This study aims to determine the effectiveness of using stick pouch media in increasing thematic learning motivation of class IIB students at SDN Pannara Makassar City. The approach used is a quantitative approach with this type of experimental research with a one group pretest posttest research design. The population in this study were all grade II SDN Pannara Makassar City, totaling 60 students. The sample in this study was class IIB students at SDN Pannara Makassar City, totaling 30 students consisting of 16 boys and 14 girls. The instruments used are observation sheets, questionnaires, tests and documentation. Data were analyzed descriptively and inferentially. The results of the research on descriptive analysis showed that the average value of teacher activity was 3.3 in the good category and in student activity the average value was 3.3 in the good category. In the student learning motivation variable, the average student result is 3.107 for the pretest and 3.613 for the posttest. Meanwhile for the stick pouch media variable, the average value was 2.580 in the pretest and 3.180 in the posttest. Inferential analysis shows a significance value of 0.000 0.05 which means that stick pouch media is effective in increasing thematic learning motivation of class IIB SDN Pannara Makassar City.